시간 기반 분리 도입을 통한 제주국제공항 활주로 처리량 개선 - 이예찬; Yechan Lee; 최상일; Sangil Choi; 김휘양; Huiyang Kim (한국항행학회논문지, 2025)
감시 시스템을 활용한 거리 기반의 분리는 도착 항공기 간 주된 종적 분리 기준으로 적용됐다. 거리 기반 분리는 기상 조건과 관계없이 고정된 거리 기준을 적용하며, 강한 정풍으로 인해 도착 항공기의 지상 속도가 감소하는 경우 활주로 접근 시간이 증가하고 활주로 처리량이 감소하는 문제가 발생한다. 이러한 문제를 개선하는 방안으로 일정한 시간 간격을 유지하는 시간 기반 분리를 최종 접근 구간에 적용하는 개념이 제시되었다. 본 연구는 제주국제공항을 대상으로 시간 기반 분리의 적용 가능성과 효과성을 평가하기 위한 목적으로 진행되었다. 통계 검정을 통해 거리 및 시간 분리에 대한 정풍 성분의 영향성을 확인하였으며, 접근 구간을 세분화하고 구간별 속도 데이터를 복원 추출하여 정풍 성분에 따른 항공기 접근 시간 및 활주로 처리량 변화를 도출하였다. Distance-based separation using surveillance systems has been applied as the primary longitudinal separation standard between aircraft. The current distance-based separation applies fixed values regardless of wind conditions, which leads to increased approach times and reduced runway throughput when aircraft approach the runway with strong headwinds that decrease their ground speed. To address the shortcomings of distance-based separation, the concept of time-based separation (TBS) has been proposed, which applies a constant time interval regardless of wind conditions. This study investigates the feasibility and practical effects of introducing TBS at Jeju International Airport in two stages. First, statistical tests were conducted to identify the impact of wind speed on both distance- and time-based separation. Second, the approach segment was subdivided, and speed data for each segment were reconstructed to compare approach times under varying wind conditions, thereby estimating the hourly runway throughput.